Ethics & values in construction industry from Islamic perspective - Al-Zahraa Sami, Fatma; Abdul Rahim, Asiah (Malaysian Institute Of Planners, 2017)
The purpose of this paper is to explore the principles of Islamic ethics to be applied in construction projects by establishing Islamic ethical practices to improve project performance. In an Islamic system, ethics and construction business are inextricably linked. This paper aims primarily to identify the ethics in general and from the Islamic perspective, and to identify the principles of Islamic ethics in construction projects. The methodology of was content analysis of peer-reviewed empirical studies published in academic journals. In addition, specialist texts to review the principles of Islamic ethics in construction projects in order to give an overview of main ethics theories. This paper will discuss the impact of Islamic ethics on performance jobs and project outcomes. Finally, this study also shows how construction companies could adapt the Islamic ethics and create Islamic ethical work climate in their projects and in society as well. In conclusion, implementation of the recommended solutions can minimize unethical acts in the construction projects.